Guidelines for the use of the International Classification of Radiographs of Pneumoconioses of the International Labour Office (ILO): Substantial changes in the currrent edition - Maja Muszyńska-Graca; Beata Dąbkowska; Piotr Z. Brewczyński (Nofer Institute of Occupational Medicine, 2016)
The International Classification of Radiographs of Pneumoconioses is the scheme worked out by the International Labour Office in Geneva (ILO), to register radiographic chest abnormalities in a well-ordered, reproducible and comparable way. It is used for diagnosing abnormalities caused by dust exposure. Guidelines for the use of the ILO International Classification of Radiographs of Pneumoconioses contain detailed information and recommendations on how to use the classification, as well as how the chest X-ray examination should be performed and recorded. To facilitate the diagnosis of observed abnormalities the classification is completed by the set of standard radiograms illustrating typical irregularities referring to lungs and pleura, included in the classification. The article presents the key information on classification and the most important amendments adopted in the 2000 and 2011 ILO guidelines revisions. These changes refer to radiographs quality assessment, the way of presenting abnormalities registered in standard radiographs (QUAD set, digital images) and registration of failures not related to dust exposure. Particularly important complements result from the development of radiological imaging techniques. They are concerned about the classification of radiographic images of the chest recorded digitally. Med Pr 2016;67(6):833-837